Entomological survey of the potential vectors of Rift Valley fever virus and absence of detection of the virus genome from the vectors in various niches in the southern half of the Great Rift Valley of Ethiopia. Issue 6 (14th September 2022) - Jaleta, Megarsa Bedasa; Tefera, Mehari; Negussie, Haileleul; Mulatu, Tesfaye; Berhe, Tsega; Belete, Fasika; Yalew, Bekele; Gizaw, Oda; Dabasa, Golo; Abunna, Fufa; Regassa, Fikru; Amenu, Kebede; et al.
Abstract: Background: Rift Valley fever virus (RVFV) is the cause of one of the most important mosquito‐borne emerging diseases negatively affecting the health of humans and animals, particularly in Africa. In Ethiopia, the status of RVFV and the existence of potential vectors are unknown. Objectives: This study aimed to survey the mosquito vectors of RVFV and the detection of the virus in selected sites (Batu, Hawassa, Arba Minch and Borana) in Ethiopia. Methods: CDC light traps baited with the sugar‐yeast solution were set up at various locations for a total of 29 trap nights. Mosquitoes identification were made morphologically using a stereomicroscope and for RVFV detection by reverse transcriptase‐polymerase chain reaction (RT‐PCR). Results: Among a total of 132 trap efforts conducted, 60 (45%) captured the mosquitoes. A total of 1576 adult mosquitoes were collected and identified. Including Aedes ( n = 407; 25.8%), Anopheles ( n = 493; 32.3%), Culex ( n = 466; 29.6%) and Mansonia ( n = 210; 13.32%). The genome material of RVFV was not detected by RT‐PCR. Conclusions: The existence of a potential Aedes species may pose a risk for the occurrence of the RVF outbreak in Ethiopia. Based on the current study, we recommend further monitoring for potential mosquito vectors of RVFV, particularly with a view to targeting the seasons during which the mosquitoes can be abundant along with a serological survey of susceptible hosts. Abstract : Potential mosquito vectors of Rift Valley Fever virus were collected and identified in Ethiopia, however, the virus genome was not detected from the mosquito pools.